Silencing and silence in Negev Bedouin students' narrative discourse. Issue 4 (4th July 2019) - Gribiea, Adnan; Ben-Asher, Smadar; Kupferberg, Irit
ABSTRACT: This article explores explicit and implicit dimensions of identity that Negev Bedouin students position in their life stories. The literature review probes the participants' historical, cultural and social contexts and presents the critical discourse-oriented perspective adopted in the study to explore identity construction in narrative discourse. Fourteen men and 16 women attending a college of education in southern Israel were asked to write meaningful stories related to various chapters in their lives. Interpretation of explicit themes and silences show that women and men positioned themselves as two separate groups vis-à-vis the male-dominated Bedouin tradition, and the Israeli government.